Mesh Erosion and Sigmoido-vaginal Fistula - Bajracharya, Nishma; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Paudel, Rekha; Joshi, Bijendra Dhoj; Joshi, Arbin (Nepal Journal of Obstetrics and Gynaecology, 2018)
Abdominal sacro-colpopexy (ASC) is a commonly performed procedure for the surgical treatment of pelvic organ prolapse (POP). Surgeons favor this technique because of its well-established success rates ranging from 78-100% and durability, which is attributed to reinforcement of native tissues with a graft. Despite recognition of the risk of erosion, synthetic grafts have been preferred over autologous grafts for ASC because they are durable, avoid the morbidity and operative time of harvesting fascia, are readily available and are relatively inexpensive. Ideally, these benefits should outweigh the possibility of erosion, which is a unique complication of using a graft. We present here a unique case of mesh erosion into bowel after ASC who presented with sigmoido-vaginal fistula.